Metallurgical and structural investigation on SS316L specimens manufactured by additive manufacturing using SLM - Taufek, Thoufeili; HP Manurung, Yupiter; Lueder, Stephan; Mingu, Zaidi; HS Pengadau, Fetisia (International Journal of Engineering and Technology, 2018)
As one of additive manufacturing (AM) technologies, selective laser melting (SLM) which uses higher energy input enabling fully molten powder bed materials is nowadays increasingly applied to build full dense components without post processing. In the present work, specimens made of stainless steel powder SS 316L were to be processed using SLM 280 HL, characterized and compared to commercial rolled sheet product with similar material and shape. The powders have been melted to form dog-bone specimen with two build up orientation using fixed major process parameters such as laser power, hatching distance and layer thickness as well as scan speed. The characterization starts with the mechanical properties and followed by microstructural analysis. While tensile strength and elongation were the main concern on mechanical properties to be discussed based on rolling and layer direction, the macro and micro analysis will focus on grain structure and fracture surface as well as the process quality. The material characterization was conducted using tensile test, optical microscopy and scanning electron microscopy. It is found out that the built-up direction, inclination angle and process quality play a big role on ductility and distortion using SLM. Although the rolled specimen showed significant difference of material strength compared to AM, the rolling direction however does not give conclusive results which can be referred to. It is expected that this basic characterization study will provide basic information and estimation towards the strength of material and final quality product prior to commencement of real product manufacturing.Â Â